Applying Extenics Theory to Motion Performs Evaluation of Numerical Machines - Chen Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The motion performs evaluation indexes of numerical control machine tools (NC) are made of multiple elements. In order to evaluate motion performs of numerical control machine tools objectively, we have applied the extenics theory to establish the matter-element model for the motion performs evaluation of the NC. The relational degree was calculated by introducing the relational function in the extension set theory, and the evaluation indexes weight coefficient of NC were defined by using the 1-9 scale law in AHP (the analytic hierarchy process). A numerical control machine tool as a study object, the motion performs was studied by using the extenics theory. The result indicates that the extenics theory is appropriate for the motion performs evaluation .The motion performs of the evaluated NC was good, the evaluation method possesses a certain practicability.